2001
DOI: 10.1186/1471-2407-1-18
|View full text |Cite
|
Sign up to set email alerts
|

Return to fertility after extended chemical castration with a GnRH antagonist

Abstract: BackgroundAntagonistic analogues of GnRH for the treatment of prostate cancer may be used clinically in persons for whom return to fertility after such treatment is important or desirable. The purpose of this study was, therefore, to evaluate the effects of a long term treatment with orntide, a GnRH antagonist, on testosterone levels and fertility in male rats.MethodsTwo groups of male rats received either 120-day orntide microspheres (8.8 mg orntide/kg/120 days) or vehicle alone (control group). Serum orntide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…However, apparent increase in overall abundance of urinary proteins by day 107 was clearly concomitant with the several-fold increase in circulating testosterone, if urine evidence at least roughly reflects the situation in its blood plasma source. Nevertheless, the present urine values of ~ 6 ng/ml are close to the 4 ng/ml reported for whole blood by radioimmunoassay in 6 month old Dark Agouti, Wistar and Sprague-Dawley males [23], and ~ 5 ng/ml, also by radioimmunoassay, in adult Sprague-Dawley rat serum [24]. However, we recognise that any further monitoring of circulating testosterone, particularly in pre-pubertal rats, should optimise urine sample collection to avoid any evaporation.…”
Section: Discussionsupporting
confidence: 82%
“…However, apparent increase in overall abundance of urinary proteins by day 107 was clearly concomitant with the several-fold increase in circulating testosterone, if urine evidence at least roughly reflects the situation in its blood plasma source. Nevertheless, the present urine values of ~ 6 ng/ml are close to the 4 ng/ml reported for whole blood by radioimmunoassay in 6 month old Dark Agouti, Wistar and Sprague-Dawley males [23], and ~ 5 ng/ml, also by radioimmunoassay, in adult Sprague-Dawley rat serum [24]. However, we recognise that any further monitoring of circulating testosterone, particularly in pre-pubertal rats, should optimise urine sample collection to avoid any evaporation.…”
Section: Discussionsupporting
confidence: 82%
“…The complete normalization of the sperm count must be viewed against the background that he was medically castrated when RT was started and remained so during the course of RT. In rats, medical castration has been shown to protect the germinative epithelium against the damaging effect of cytostatics and RT [14–16]. This has not been confirmed in patients with testicular cancer and malignant lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, 8.8 mg/kg subcutaneous injections of orntide formulated in microspheres suppressed testosterone levels below 5 ng/ml for approximately 150 days. Return to fertility was demonstrated at day 269 after injection [34]. Although not published, a Phase I trial demonstrated dose-dependent hormone suppression, with 4 mg of free peptide injected daily for seven days rendering all subjects castrate by day seven; testosterone levels returned to baseline 14 days after the last injection.…”
Section: Gnrh I Receptor Gnrh Ii Receptormentioning
confidence: 99%